Patient participation in free cataract surgery: a cross-sectional study of the low-income elderly in urban China. Issue 4 (15th April 2016) - Lin, Haotian; Lin, Duoru; Long, Erping; Jiang, Haofeng; Qu, Bo; Tang, Jinzhu; Lin, Yingfen; Chen, Jingjing; Wu, Xiaohang; Lin, Zhuoling; Li, Xiaoyan; Liu, Zhenzhen; et al.
Abstract : Objectives: To explore the characteristics of the low-income elderly who underwent free cataract surgery and to determine the degree of patient satisfaction with the free cataract surgery programme in urban China. Methods: A free cataract surgery management workflow was designed as a poverty relief project in Guangzhou. In this study, participants who underwent free cataract surgery between January and August 2014 received a telephone interview based on a structured questionnaire. Data were collected on patient demographics, resources, health conditions, reasons for undergoing the free surgery and overall evaluation of the free cataract surgery programme. Results: Among the 833 participants, the mean surgical age was 76.85±7.46 years (95% CI 76.34 to 77.36), and the male to female ratio was 385:448. The majority (94.31%, 746/791) of patients resided in the main urban districts. Patients underwent surgery 61.08±60.15 months (95% CI 56.17 to 66.00) after becoming aware of the cataract, although 66.83% of them reported that their daily lives were influenced by cataracts. Only 21.5% of the respondents underwent physical examinations that included regular eye screening, and only 6.30% were highly educated patients. Financial problems were the primary reason cited by patients for participating in the free surgery programme. Those patients with a monthly family income of 1000–2999¥ (US161–482) per capita constituted the largest patient population. The free clinics in the parks and the free cataract surgery were highly rated (9.46 and 9.11 of 10 points) by the beneficiaries. Conclusions: The telephone survey revealed a high level of patient satisfaction regarding the free cataract surgery programme. Most of the patients who participated in the programme resided in major urban districts and had poor health awareness and a low level of education. The information provided by this study is crucial for improving and expanding the management of free cataract surgery programmes. Trial registration number: NCT02633865; Post-results.